PEMBUATAN NATRIUM ALGINAT DARI ALGA COKLAT (Phaeophyta) DAN PENGARUH PENAMBAHANNYA PADA SIFAT ANTIBAKTERIAL SABUN MINYAK DEDAK PADI (RICE BRAN OIL) - Setyoaji, Muhammad Ilham; Subehi, Muhammad; ., Susanty; Nugrahani, Ratri Ariatmi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
Indonesia is a country with abundant natural resources that support its economic growth. One of the natural resources of Indonesia is Sargassum sp, a genus of brown algae (Phaeophyta). Alginate is the main constituent of the cell walls, is composed of calcium salts, magnesium, sodium, and potassium alginate. The purposes of this study were to synthesize Sodium Alginate, to analyze the effect of NaOH concentration, to characterize and identify, as well as to apply as emulsifier, dispersant therefore it affect an antibacterial properties of Rice Bran Oil bar soap, RBO. As the research method, the extraction of Alginate was conducted through the acid pathway with the concentration of NaOH varied into 2%, 4%, 8%, 10%, and 12%,  cell disruption with 1% of HCI, extraction with 4% of Na 2 CO 3 , and conversion into alginic acid with the addition of 10% of HCI. The conversion of alginic acid into Sodium Alginate was conducted by adding NaOH. The addition of isopropyl alcohol was done for the purification. The product characterization was carried out on the pH and water content, while the identification was performed by using FTIR. Then, an evaluation was done for the application of antibacterial properties on RBO bar soap. The results of this study showed that the best condition was indicated from the addition of 4% NaOH concentration with 10.95% yields, 5-9 pH level, as well as 3.3% - 36.67% water content. The result of FTIR analysis indicated that the product obtained was Sodium Alginate with asymmetric group COO, hydroxyl group OH , and symmetric group COO. The evaluation result of Sodium Alginate  on the antibacterial properties of rice bran oil bar soap indicated an ineffective result in inhibiting bacterial growth. Keywords :  Brown algae, FTIR, Sodium Alginate, Sodium Hydroxyde